Broad band plasmonic nanomaterials for high performance solar cells. Issue 3 (21st December 2015) - Sung, Yun-Ming; Lai, Ying-Chih; Tsai, Ming-Fong; Hsieh, Hsing-Hua; Yang, Min-Han; Wei, Philander Penn; Yeh, Chen-Sheng; Hsu, Fang-Chi; Chen, Yang-Fang
Abstract : A large enhancement in the performance of solar cells, arising from plasmonic nanomaterials with a broad band absorption spectrum, is proposed. Abstract : A large enhancement in the performance of solar cells, arising from plasmonic nanomaterials with a broad band absorption spectrum, is proposed. Gold nanorod-in-shell (Au NR-in-shell) nanomaterials can absorb photons covering the UV-visible-NIR region in contrast to the two distinct narrow peaks for bare Au NRs. The broad localized surface plasmon resonance (LSPR) induced light absorption enhancement as well as series resistance, carrier lifetime and device mobility for devices containing Au NR-in-shells are superior than those for Au NR devices. To illustrate our working principle, we implemented Au NR-in-shells in polymer solar cells, which resulted in high efficiency. This led to the realization of polythieno[3, 4- b ]-thiophene/benzodithiophene:[6, 6]-phenyl C71 butyric acid methyl ester (PTB7:PC71 BM) polymer solar cells (PSCs) with a power-conversion-efficiency (PCE) of 9.01%, which is more than twice the enhancement for that of Au NRs incorporated cells and sets the highest record reported to date for PTB7 based inverted devices adopting the plasmonic light trapping strategy. Our approach shown here is a key step for the further development of high performance optoelectronic devices.